PENGARUH PERBANDINGAN AIR KELAPA DAN SARI SIRSAK TERHADAP KUALITAS MINUMAN BERKARBONASI DENGAN PENAMBAHAN NaHCO3 - Marlina, Lusi; Wijayanto, Yulfan (Jurnal TEDC; Vol 18 No 2 (2024): JURNAL TEDC, 2024)
Carbonated drinks have a sparkle effect with a typical soda taste in the mouth and generally use artificial flavors. Rarely use natural flavors. A new innovation in the manufacture of carbonated drinks is using coconut water as raw material with the addition of soursop fruit juice which is a natural flavor. Making carbonated drinks from coconut water and soursop juice is done by using sodium bicarbonate (NaHCO 3 ) as a producer of CO 2 gas. This study aims to determine the effect of the ratio of coconut water to soursop extract and sodium bicarbonate concentration to produce carbonated drinks with good quality. This study used a completely randomized design (CRD) with 2 factors, namely the ratio of coconut water to soursop extract and the concentration of sodium bicarbonate. The results showed that the highest levels of vitamin C were in KS 1 N 1 with a ratio of coconut water: soursop essence (50: 50) and 0.7% NaHCO 3 , with vitamin C levels (26.4 mg/100 g) which were still acceptable TKPI Ministry of Health 2019, value total acid (0.282%) according to SNI 3719:2014, and the pH value (4.33) according to SNI 3708:2015. The best organoleptic results were for KS 4 N 1 with a ratio of coconut water: soursop extract (80: 20) and 0.7% NaHCO 3 with an organoleptic value of taste 4.7 (like), aroma 3.3 (rather like) and color 4.3 (like) . The results showed that the ratio of coconut water and soursop extract affects the quality of carbonated drinks.